Time Preferences and Medication Adherence: Evidence from Pregnant Women in South Africa - Kai Barron; Mette Trier Damgaard; Christina Gravert; Lisa Norrgren (Center for Economic Studies and ifo Institute (CESifo), 2022)
The effectiveness of health recommendations and treatment plans depends on the extent to which individuals follow them. For the individual, medical adherence involves an inter-temporal trade-off between expected future health benefits and immediate effort costs. Therefore examining time preferences may help us to understand why some people fail to follow health recommendations and treatment plans. In this paper, we use a simple, real-effort task implemented via text message to elicit the time preferences of pregnant women in South Africa. We find evidence that high discounters are significantly less likely to report to adhere to the recommendation of taking daily iron supplements daily during pregnancy. There is some weak indication that time inconsistency also negatively affects adherence. Together our results suggest that measuring time preferences could help predict medication adherence and thus be used to improve preventive health care measures.
Keywords: C93; D91; I12; 330; time preferences; medication adherence; experiment